Silk nanoparticles for the protection and delivery of guava leaf (Psidium guajava L.) extract for cosmetic industry, a new approach for an old herb - Duy Toan Pham; Doan Xuan Tien Nguyen; Ruby Lieu; Quoc Cuong Huynh; Ngoc Yen Nguyen; Tran Thi Bich Quyen; Van De Tran (Taylor & Francis Group, 2023)
AbstractGuava (Psidium guajava L.) is a well-known plant containing high levels of natural antioxidants, the phenolic compounds, which have been employed in numerous cosmetic products. However, these molecules are unstable to oxidants, light, temperature, pH, water, and enzymatic activities. Therefore, to enhance their stability and preserve their antioxidant activity, this study investigated the silk fibroin nanoparticles (SFNs) ability to encapsulate, deliver, and heat-protect the phenolic compounds of the guava leaves ethanolic extract. Firstly, the guava ethanolic extract was produced by maceration, which possessed a total phenolic content of 312.6 mg GAE/g DPW and a high antioxidant activity (IC50 = 5.397 ± 0.618 µg/mL). Then, the extract loaded SFNs were manufactured by desolvation method, and the particles demonstrated appropriate sizes of 200-700 nm with narrow size distribution, spherical shape, silk-II crystalline structure, high drug entrapment efficiency of > 70% (dependent on the fibroin content), and a two-phase sustained drug release for at least 210 min. Using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, the antioxidant activity of the guava extract was well-preserved in the extract loaded SFNs. Finally, after being treated with high temperature of 70 °C for 24 h, the guava extract almost loses all of its antioxidant property (5 times decrement), whereas the extract loaded SFNs could retain the extract activity. Conclusively, the SFNs proved much potential to deliver and heat-protect the guava extract phenolic compounds, and preserve their antioxidant activity. Confirmed by this case, SFNs could be further explored in protecting other natural compounds from environmental factors.